The development of the Japanese version of the compassionate engagement and action scales - Asano, Kenichi (2020)
The last few years have seen increasing research on self-report measures of compassion. The Compassionate Engagement and Action Scale (CEAS) is rooted in an evolutionary approach to compassion, which focuses on the competencies of compassion those are engagement with distress or suffering, and taking action to alleviate and prevent it. This study sought to validate the CEAS in a Japanese population using a cross-sectional design. A total of 279 students (82 males, 191 females, 6 unknown) answered self-report questionnaires, including the Japanese version of CEAS. We found single-factor structures for compassion for others scales, compassion from others scales, and compassion for self scales. All scales were found to have acceptable internal consistency, test-retest reliability, content validity, and construct validity. Even though some limitations, these results indicate that the Japanese version of CEAS is an adequately constructed and useful measure to assess compassionate engagement and action toward others, from others, and for the self with Japanese population.